(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
This study aims to identify reading anxiety among secondary school students. The research design employed a quantitative approach in the form of a survey study. There were 80 respondents who were willing to participate in this study. The respondents were students from one of secondary in the Niger Delta Region. All respondents were students from junior secondary school classes. To collect the data, this study adapted a questionnaire from Ahmad et.al. (2013) which consists of five domains of reading anxiety, i.e., (1) lack of vocabulary, (2) unfamiliar topic, (3) unfamiliar culture, (4) afraid of making errors, and (5) worry about reading effects. Based on the results, the statement with the highest score is “I enjoy reading a text in English text in English when I know its translation” (M=4.15; SD=.730). Meanwhile, the statement with the lowest score is “In reading aloud in the class I do not understand the text even though it is easy” (M=3.00; SD=1.055). The data imply that the most significant factor in students’ reading anxiety is lack of vocabulary and the least factor is worrying about reading effects.